Development of Flashcard Media on Students' Learning Motivation - Afifah Rizki, Nur; Paramitha, Ielda; Darmadi, I Wayan; Jarnawi, Muhammad (Al-Khazini, 2026)
This study aims to develop and design flashcard-based learning media that can enhance students' motivation to learn. The research employs the Research and Development (R&D) method with the ADDIE development model, which includes the stages of Analyze, Design, Development, Implementation, and Evaluation. The flashcard media was designed using the Canva platform for visual design and Assembler Edu for AR content integration. Validation was conducted by subject matter experts and media experts. The trial involved 20 students and 3 science teachers, with data collected through learning motivation questionnaires, student and teacher response questionnaires, and pretest-posttest assessments. The validation results showed a media expert score of 4.59 (very feasible) and a subject matter expert score of 3.50 (feasible). The responses from teachers and students were categorized as very feasible, with scores of 4.41 and 4.37, respectively. Students' learning motivation increased, with a score of 4.02 (high category) and an N-Gain of 72.34% (high category). The media also proved effective in improving students' understanding, as seen in the increase in the average posttest score (77.95) compared to the pretest score (20.9). The study concludes that this AR-based flashcard media is feasible, practical, and effective as an innovative learning tool. Recommendations for further research include improving the quality of physical materials (lamination) and expanding the development to other physics topics.